The Legal Politics of Regulating Indigenous Peoples - Kenneth Adriel; Tania Winata; R.A Steffie Rossellini; Jeane Neltje (Yayasan Adra Karima Hubbi, 2023)
Background. This research raises the issue of the existence of customary law communities in Indonesia, as well as the dynamics of customary law communities seen from the decision of the Constitutional Court. Purpose. This research is focused on analyzing two things, namely: First, what is the existence of indigenous peoples in Indonesia? Second, how is the legal politics of indigenous peoples through the decision of the Constitutional Court? This research uses a statute approach. Method. his research uses a statute approach. In addition, a case approach is also used to find out the ratio decidendi used by the Constitutional Court judges in deciding cases of judicial review of laws related to indigenous peoples. Results. The results of the study concluded: first, the existence of indigenous peoples in Indonesia has been accommodated in various spheres of legislation, both in the 1945 Constitution, Laws, Regional Regulations, Governor Decrees, and Regent Decrees. Second, the legal politics of indigenous peoples through the decision of the Constitutional Court strengthens the existence of indigenous peoples in Indonesia by providing various interpretations or explanations. Conclusion. this study are that the Panel of Judges in cases of criminal acts of narcotics abuse should minimize criminal disparities to prevent the development of a negative perspective of society towards the criminal system in judicial institutions.